Dynamical and thermodynamical aspects of precipitation events over India. (22nd October 2021) - Kumari, Amita; Kumar, Pankaj; Dubey, Aditya Kumar; Mishra, Alok Kumar; Saharwardi, Md. Saquib
Abstract: This study examines different precipitation events (PEs) for 1951–2015 using 0.25°×0.25° India Meteorological Department data and diagnoses their associated dynamical and thermodynamical processes during the summer monsoon season over India using ERA5 reanalysis. Our results reveal a significant decreasing trend of mean precipitation, rain event days, light rain events and moderate rain events (MREs) for the overall period. However, the frequency of heavy rain events (HREs) and very heavy rain events (VhREs) has increased. Pettit's test for all PEs and mean precipitation indicates the changes nearly in the 1970s. In spite of this, the rate of change of LREs, MREs and HREs was increased by 17, 91 and 114% after the observed change point with respect to before change point, while for VhREs, this was reduced by 50%. These decreasing (increasing) trends of LREs (VhREs) are attributed to both thermodynamical and dynamical conditions. LREs are driven mainly by convective precipitation having a contribution of 79%, whereas large‐scale precipitation contributes 56% to the VhREs. It is observed that the dynamical (thermodynamical) effect largely drives VhREs (LREs) PEs. During VhREs, stronger moisture‐laden low‐level jet (LLJ) from the surrounding ocean converges over the Indian land mass, facilitating favourable conditions for enhanced precipitation. Simultaneously, weaker convective available potential energy (CAPE) during the VhREs underlines inconstancy in thermodynamics. Stronger LLJ and weaker CAPE during the extremes and vice versa for LREs highlight the dominance of the dynamical (thermodynamical) effect during the VhREs (LREs). Abstract : Graphical representation of the mechanisms associated with the light and very heavy rain events (LREs and VhREs). It has been found that mean precipitation is decreasing over Central India. However, VhREs are increasing over the region. The LREs are dominated by convective rainfall while the VhREs by a large scale. Thus, it was observed that low‐level circulation controls the VhREs and convective instabilities govern LREs. Moisture fluxes are found to be weaker, leading to less transport.